Lactate Promotes Myoblast Differentiation and Myotube Hypertrophy via a Pathway Involving MyoD In Vitro and Enhances Muscle Regeneration In Vivo - Sakuka Tsukamoto; Ayako Shibasaki; A. Naka; Hazuki Saito; Kaoruko Iida (2018)
Lactate is a metabolic substrate mainly produced in muscles, especially during exercise. Recently, it was reported that lactate affects myoblast differentiation; however, the obtained results are inconsistent and the in vivo effect of lactate remains unclear. Our study thus aimed to evaluate the effects of lactate on myogenic differentiation and its underlying mechanism. The differentiation of C2C12 murine myogenic cells was accelerated in the presence of lactate and, consequently, myotube hypertrophy was achieved. Gene expression analysis of myogenic regulatory factors showed significantly increased myogenic determination protein (MyoD) gene expression in lactate-treated cells compared with that in untreated ones. Moreover, lactate enhanced gene and protein expression of myosin heavy chain (MHC). In particular, lactate increased gene expression of specific MHC isotypes, MHCIIb and IId/x, in a dose-dependent manner. Using a reporter assay, we showed that lactate increased promoter activity of the MHCIIb gene and that a MyoD binding site in the promoter region was necessary for the lactate-induced increase in activity. Finally, peritoneal injection of lactate in mice resulted in enhanced regeneration and fiber hypertrophy in glycerol-induced regenerating muscles. In conclusion, physiologically high lactate concentrations modulated muscle differentiation by regulating MyoD-associated networks, thereby enhancing MHC expression and myotube hypertrophy in vitro and, potentially, in vivo.